2018
DOI: 10.1021/acs.jafc.7b04779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chain Length and Degree of Unsaturation of Fatty Acids on Structure and in Vitro Digestibility of Starch–Protein–Fatty Acid Complexes

Abstract: The effects of chain length and degree of unsaturation of fatty acids (FAs) on structure and in vitro digestibility of starch-protein-FA complexes were investigated in model systems. Studies with the rapid visco analyzer (RVA) showed that the formation of ternary complex resulted in higher viscosities than those of binary complex during the cooling and holding stages. The results of differential scanning calorimetry (DSC), Raman, and X-ray diffraction (XRD) showed that the structural differences for ternary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
147
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(170 citation statements)
references
References 45 publications
(80 reference statements)
13
147
1
Order By: Relevance
“…A model system containing sorghum starch, whey proteins, and FAs (palmitic acid [PA], oleic acid, or linoleic acid) showed a prominent viscosity peak during the RVA cooling (i.e., setback) stage and a HPSEC peak that eluted between the amylose and amylopectin peaks; these observations were attributed to the formation of starch–lipid–protein complexes (Zhang & Hamaker, 2004; Zhang et al., 2003). Subsequent studies using different starch–lipid–protein mixtures confirmed the formation of ternary complexes (Shah et al., 2011; Wang et al., 2017; Zhang & Hamaker, 2004; Zhang et al., 2010, 2018). Addition of long chain FAs alone (e.g., PA, oleic acid, or linoleic acid) to starch has a small effect on final pasting viscosity during the setback stage (Figure 2a), whereas the addition of βLG to these starch–FA pasting systems led to the occurrence of a distinct viscosity peak during this stage of RVA protocol (Figure 2b).…”
Section: Basic Description Of the Formation And Structure Of Starch–lmentioning
confidence: 90%
See 4 more Smart Citations
“…A model system containing sorghum starch, whey proteins, and FAs (palmitic acid [PA], oleic acid, or linoleic acid) showed a prominent viscosity peak during the RVA cooling (i.e., setback) stage and a HPSEC peak that eluted between the amylose and amylopectin peaks; these observations were attributed to the formation of starch–lipid–protein complexes (Zhang & Hamaker, 2004; Zhang et al., 2003). Subsequent studies using different starch–lipid–protein mixtures confirmed the formation of ternary complexes (Shah et al., 2011; Wang et al., 2017; Zhang & Hamaker, 2004; Zhang et al., 2010, 2018). Addition of long chain FAs alone (e.g., PA, oleic acid, or linoleic acid) to starch has a small effect on final pasting viscosity during the setback stage (Figure 2a), whereas the addition of βLG to these starch–FA pasting systems led to the occurrence of a distinct viscosity peak during this stage of RVA protocol (Figure 2b).…”
Section: Basic Description Of the Formation And Structure Of Starch–lmentioning
confidence: 90%
“…Addition of long chain FAs alone (e.g., PA, oleic acid, or linoleic acid) to starch has a small effect on final pasting viscosity during the setback stage (Figure 2a), whereas the addition of βLG to these starch–FA pasting systems led to the occurrence of a distinct viscosity peak during this stage of RVA protocol (Figure 2b). The addition of βLG to pasting systems containing starch and medium chain FAs (e.g., lauric acid [LA] and decanoic acid) increases the intensity of the cooling stage viscosity peak, compared to the corresponding starch–FA mixture (Figure 2c) (Wang et al., 2017; Zheng et al., 2018). These studies further confirmed that starch, FAs, and protein can form ternary complexes during a heating–cooling process.…”
Section: Basic Description Of the Formation And Structure Of Starch–lmentioning
confidence: 99%
See 3 more Smart Citations